2013
DOI: 10.1177/1098612x13492739
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of urinalyses from untreated adult cats with lower urinary tract disease and healthy control cats: predictive abilities and clinical relevance

Abstract: This case-controlled study evaluated urinalyses from 111 primary cases diagnosed with feline lower urinary tract disease (FLUTD) and 101 healthy control cats. Urine samples were analysed by standardised procedures, and differences between the two groups were compared by multivariable logistic regression analysis, while controlling for age, body weight, gender and reproductive status. Further, the ability of using urine sediment findings to predict bacteriuria was evaluated. In addition, urinalyses from cats wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 37 publications
2
51
1
3
Order By: Relevance
“…To our knowledge, this study was the first to describe the prevalence of CaOx crystalluria in dogs with CaOx uroliths. In a retrospective study 26 of cats with lower urinary tract disease, crystalluria was present in 4 of 13 (31%) cats with urolithiasis, 34 of 59 (58%) cats with idiopathic cystitis, and 6 of 14 (43%) cats with bacterial cystitis. The types of crystals and uroliths identified in the cats of that study 26 were not reported, which hinders interpretation of those results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To our knowledge, this study was the first to describe the prevalence of CaOx crystalluria in dogs with CaOx uroliths. In a retrospective study 26 of cats with lower urinary tract disease, crystalluria was present in 4 of 13 (31%) cats with urolithiasis, 34 of 59 (58%) cats with idiopathic cystitis, and 6 of 14 (43%) cats with bacterial cystitis. The types of crystals and uroliths identified in the cats of that study 26 were not reported, which hinders interpretation of those results.…”
Section: Discussionmentioning
confidence: 98%
“…In a retrospective study 26 of cats with lower urinary tract disease, crystalluria was present in 4 of 13 (31%) cats with urolithiasis, 34 of 59 (58%) cats with idiopathic cystitis, and 6 of 14 (43%) cats with bacterial cystitis. The types of crystals and uroliths identified in the cats of that study 26 were not reported, which hinders interpretation of those results. The low proportion of dogs with CaOx crystalluria in the present study could have been a reflection of sample handling.…”
Section: Discussionmentioning
confidence: 98%
“…A wide range of prevalence rates for subclinical bacteriuria has been reported in cats, varying from low rates of <1.0%‐3.3%, 12,34,35 to intermediate rates of 6.1, 7.9, and 10%‐13%, 26,27,36 to a high rate of 28.8% 11 . The main difference in these studies was the age of the cats, which tended to be younger in the studies with lower prevalence rates 12,34,35 and older in the studies with prevalence rates >6% 11,26,36 .…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] DNA preparation DNA was isolated from 200 µl well-mixed non-sedimented urine using the QIAamp DNA mini kit (Qiagen) following the manufacturer's instructions, with the exception of the amount of elution buffer used in the final steps. A reduced volume of 50 µl elution buffer was used in order to increase the final DNA concentration in the eluate.…”
Section: Methodsmentioning
confidence: 99%